Dampak Program Kampus Mengajar Terhadap Keterampilan Pemberian Layanan Bimbingan Konseling di Sekolah Dasar: Studi Kualitatif pada Mahasiswa BKI Universitas Al-azhar Indonesia - Anisa Rahmadani; Syariful Syariful; Oca Restavia (Universitas Al Azhar Indonesia, 2022)
Kampus Mengajar as a part of Merdeka Belajar Kampus Merdeka (MBKM) policy is seen as an effort to advance and promote education quality. This study aims to provide a description of the extent to which the Kampus Mengajar program contributes to the skills of providing counseling and guidance services at the elementary school level. Using descriptive qualitative with purposive sampling to recruit respondents with the criteria of Islamic Counseling Guidance study program students who participate the Kampus Mengajar program batch I and 2 (n = 9). The data analysis technique uses theme analysis. Results found additional skills that respondents acquired during the assignment of the Kampus Mengajar program is communication skills, open learning skills, report cards building skills, observation skills, and increased ability to empathize. The results of the study also show that in practice the Teaching Campus program provides space to practice the skills of implementing guidance and counseling services in primary schools.Keywords - Guidance and counseling, Kampus mengajar, Primary school.